The linguistic-discursive actions in the legal speech: a vision on the image of the woman in the crimes against the customs of the criminal code - Moraes, Carla Roselma Athayde; Guimarães, Gustavo Miranda; Silva, Priscilla Chantal Duarte; Marchesani, Silvana (Laboratório Editorial FCL-UNESP, 2008)
This article presents an analysis of the image of the woman treat some articles in Brazilian Penal Code. We used from some Analyze Discourse theories discussing about discursive formation, action, rationality and intentionally. With this theoretic field, this work discusses some linguistic-discursive questions able to construct a Brazilian woman image in the Penal Code.